2021
DOI: 10.3390/buildings11080360
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Critical Success Factors (CSFs) in Management of Investment-Construction Projects: Insights from Bayesian Model Averaging

Abstract: The problem with evaluating investment projects is that there are many factors that determine the degree of their successful conclusion. Consequently, there has been an active debate for years as to which critical success factors (CSFs) contribute most to the performance of construction projects. This is because the practice of empirical research is based on two steps: first, researchers choose a particular model from the space of all possible models, and second, they act as if the chosen model is the only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Time uncertainty is ubiquitous in all disciplines of project planning and scheduling, yet in the construction industry it is of particular importance [1][2][3][4][5][6]. In particular, the uncertainty and risk associated with scheduling is an important aspect of large and complex construction projects [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time uncertainty is ubiquitous in all disciplines of project planning and scheduling, yet in the construction industry it is of particular importance [1][2][3][4][5][6]. In particular, the uncertainty and risk associated with scheduling is an important aspect of large and complex construction projects [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the uncertainty and risk associated with scheduling is an important aspect of large and complex construction projects [7][8][9][10]. In fact, successful project completion is mainly the result of a variety of multidirectional and comprehensive activities in the area of the creation of companies' intellectual capital, preparation of flexible plans and schedules, and their posterior implementation [3]. The analysis of completion times for individual activity tasks as well as entire phases/stages of the construction process should help project managers understand the factors that influence the final estimate of project duration [1,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pace [3] recognized that project success factors are important to the overall successful outcome of a project, examining a number of studies in an attempt to correlate reported project success with the chosen project management methodology, but recognizing only a weak correlation at best. Determining project success is dependent on the stakeholder's role in the project [4][5][6][7][8][9][10][11][12][13][14][15][16]. Pinto and Slevin [10] discussed the criteria for a project consisting of the following characteristics: a specified time for completion (schedule), a limited or defined budget (budget), performance expectations and a series of activities (performance), and issues dealing with the client (client satisfaction).…”
Section: Introductionmentioning
confidence: 99%
“…The defined characteristics of a project become the criteria evaluated to determine success, and if the characteristics are incomplete, a determination of project success may be incomplete or inaccurate. Critical success factors (CSFs) can help quantify the success of a project, but which CSFs contribute the most to performance and if they apply equally to all stakeholders continues to be an ongoing debate [12]. Atkinson [5] goes on to state that success must be defined beyond the simplistic "iron triangle" of cost, schedule, and quality, and should include the criteria of the information system, organizational benefits, and stakeholder community benefits.…”
Section: Introductionmentioning
confidence: 99%